(3GdehGgH GdSfjI hGdaJhMGJ GdQHGfjI aj TQM CHjGJ GdOejGWjIs - (3RQhb, CMeO Hf CMeO Hf eMeO, J(B899(3g`s ((3MehO Hf GdSjO jhSa MHhHs)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe CHh GdYHGS CMeO Hf YjSi (B((3YQa HRQhb(B) (3GdaGSj GdTGPdjGdMeO ddg Gdedc GdhgGH CeG HYO Cf CPcQ (B((3cPG(B) (3TjFG ef NhGU fXe GdTjN Gdehdi GdUGdM GdUhaj fhQ GdOjf SjOfG GdeSei HGdOejGWjs
(3BNQgG (B:s
(3hCQaY GdUQI ef JMJ GdWYGe HMjK dG jQGc CMO YfO GdhVY hdG YfO GdQaY hGdeGFOI dG JMQcgG ef ecGfgG hgh gPG GdNGJe GdTQja GdQajY GdbOjQ GdeKdhGdUdGI hGdSdGe Ydi SjOfG eMeO fHjg hNjQ Ndbg hYdi Bdg hUMGHJg CLeYjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 91s
(3eYLe GdeDdajf(B: 1 / 98s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs